Algorithms for Controlling Industrial Robots in Food Production, Including the Processes of Serialization and Aggregation of Products - Ya. S. Hurskaya (Цифровая трансформация, 2025)
Innovations in the system of mandatory labeling of goods of various categories require changes in established production processes. Every year, there is an increase in the number of installed robotic systems. Research in the field of robotics is carried out in new areas. Production processes are modernized taking into account the requirements for serialization and aggregation. The article provides a detailed analysis and a general diagram of the technological process of manufacturing food products in the dairy industry. Production using robots and the mandatory presence of a labeling module in the process of product release are considered. The stages associated with the serialization and aggregation of group containers (boxes/pallets) are described in detail. Explanations are given for the developed control algorithm diagrams that illustrate the sequence of actions of industrial robots necessary to perform serialization and aggregation operations.